Aesthetics and analysis in writing on religion : modern fascinations - Gold, Daniel, 1947- (University of California Press, 2003)
Addressing a fundamental dilemma in religious studies, this text explores the tension between humanistic and social scientific approaches to thinking and writing about religion. Daniel Gold develops a line of argument that begins with the aesthetics of academic writing in the field.